The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12905-014-0159-9
|View full text |Cite
|
Sign up to set email alerts
|

Uterine rupture disguised by urinary retention following a second trimester induced abortion: a case report

Abstract: BackgroundUterine rupture classically presents with severe abdominal pain, loss of fetal station, vaginal bleeding, and shock.Case presentationWe present a case of uterine rupture presenting as significant urinary retention that occurred following a second trimester abortion induced with mifepristone and misoprostol. Uterine rupture was discovered unexpectedly on diagnostic laparoscopy. The uterine rupture was contained by dense adhesions between the omentum and bladder with the previous uterine cesarean hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
51
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 10 publications
16
51
10
Order By: Relevance
“…VC was identified only in 7.4% of women with vaginal infection in the present study, showing a similar prevalence to a study realized in Ethiopia (8.3%) 68 . However, several countries reported a higher rate of candidiasis, more precisely, Brazil (52.4%), Italy (43.5%), India (35.0%), Nigeria (36.0%), Chile (43.9%) and USA (20–30.0%) 35 , 82 87 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…VC was identified only in 7.4% of women with vaginal infection in the present study, showing a similar prevalence to a study realized in Ethiopia (8.3%) 68 . However, several countries reported a higher rate of candidiasis, more precisely, Brazil (52.4%), Italy (43.5%), India (35.0%), Nigeria (36.0%), Chile (43.9%) and USA (20–30.0%) 35 , 82 87 .…”
Section: Discussionsupporting
confidence: 92%
“…Although few studies analyzed the presence of different types of vaginal infection in women, Jahic and colleagues 3 reported in 2013 a similar prevalence of AV (51%) in their population set, a lower rate of BV (15.0%) and a higher rate of VC (17.0%). Another study realized by Mulu et al 68 showed a more similar candidiasis rate (9.2%) as the present study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants were 30 AA women enrolled in an eight-week randomized pilot trial evaluating the effects a multi-component, culturally relevant intervention delivered using Facebook and text-messaging to promote PA among AA women versus a non-culturally tailored print-based PA intervention (Joseph et al , 2015). Eligibility for the original pilot study included: (a) self-identified as AA and female, (b) insufficiently active [ie, <150 min/week of moderate-intensity PA as assessed by the short version of the International Physical Activity Questionnaire (IPAQ)], (c) aged 24–49 years, (d) had an active Facebook account, and (e) could to read and write in English.…”
Section: Methodsmentioning
confidence: 99%
“… 7 Moreover, most cancers diagnosed in Uganda are already in advanced stage, when no remedial action can be taken. 8 Community-level factors such as: knowledge, attitudes and access to screening services can have implications for the successful implementation of screening programmes and other public health interventions. 6 9 10 Specifically, factors such as a feeling of embarrassment, perceived pain during examination, fatalism associated with a diagnosis, unsupportive husbands and lack of awareness about cervical cancer and available services can play a key role.…”
Section: Introductionmentioning
confidence: 99%